The effect of minority bank ownership on minority credit - Agustin Hurtado; Jung Sakong (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2022)
We study the effect of racial minority bank ownership on minority credit access. Using new data for 87 million minority borrowers, we present four main findings. First, minority-owned banks specialize in same-race mortgage lending. Over 70 percent of their mortgages go to borrowers of bank owners' same race. Second, the effect of minority bank ownership on minority credit is large and exceeds that of minority loan officers. We find that minority borrowers applying for mortgages in banks whose owners are of the same minority group are nine percentage points more likely to be approved than minority borrowers in non-minority banks. This effect is over six times that of a minority loan officer. Third, the default rate of minority banks' same-race borrowers is much lower than that of otherwise-identical borrowers of other races, and Asian banks drive this difference. Fourth, evidence from plausibly exogenous bank collapses suggests that the effect of Asian bank ownership might reflect an expansion rather than a reallocation of credit to Asian borrowers. Our findings are consistent with minority bank ownership reducing information frictions and improving credit allocations.
Keywords: 330